(untitled) (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
This study examines the factors that influence youth participation in legislative elections in Maros regency in 2019. The participation of youth is as participants in the election of a political party. Based on data from the Regional Election Commission (Election Commission) Maros has recorded as many as 105 young men involved as a legislative candidate Maros regency in 2019. The method used in this research is qualitative method with descriptive models. The data collection was done by interview, observation, and focus group discussion (FGD). The informants came from various backgrounds political parties and youth organizations. Determination of informants were chosen intentionally (purposive). This study was conducted in Maros, from December 2019 until February 2020. The results showed that the factors that influence youth participation in legislative elections contestation is divided into three: the idealism of youth, power relations and capital, as well as the supplementary administrative requirements. 1) pertaining to the idealism of youth and youth organizations during a student activities on campus. 2) The power relations and capital, capital utilization and the persona of the parents of the young man to come forward to fight. 3) Complementary administrative requirements, relating to the regulation of elections that take advantage of youth to participate as election participants and carried out by a political party elite as well as the supplementary administrative requirements.